MUD-BOTTOM HOLLOWS: EXCEPTIONAL FEATURES IN CARBON-ACCUMULATING BOGS? - Karofeld E. (My University, 2004)
Mud-bottom hollows are depressions on the bog surface where Sphagnum mosses have died and peat accumulation is retarded or even replaced with loss by oxidation. Results of measurements carried out at MAnnikjArve Bog, central Estonia, con” rmed that peat accumulation has stopped and that in 1999–2001 the uppermost 2–3 cm thick surface layer of mud-bottom hollows became thinner by 1.95 6 0.75 mm yr2 1 (n = 188). Different methods revealed the corresponding carbon loss from the mud-bottom hollows 25 mm thick surface layer as 50–60 g C m2 2 yr2 1. As a result, the surface of mud-bottom hollows becomes lower as compared to surroundings with peat accumulation c. 1.5 mm yr2 1, and they are likely to have an important role in the differentiation of bog microtopography. Owing to the combination of a cessation in peat accumu lation, carbon loss by oxidation and increased emission of decomposition gases, mud-bottom hollows could have an important in‘ uence on the carbon budget of bogs.
Keywords: BOG; MIRE SURFACE; CARBON LOSS; PEAT OXIDATION AND ACCUMULATION; MUD-BOTTOM HOLLOWS